Menjemput Karya Generasi Muda Dari Pucuk Sidoarjo - Suprihatin Suprihatin (Prapanca : Jurnal Abdimas, 2021)
Gebang 2 Elementary School is a remote school in Sidoarjo which is located in Pucukan Hamlet, Sidoarjo District. The school is called remote because the path taken is a narrow road, and can only be passed by motorbike. If it rains, the road to the location is impassable, due to puddles of water and mud. However, it is also possible to cross the waterway by using a boat with about 45 minutes of travel. In this school it is difficult to access the internet network, so it is not possible to do online school during the pandemic. As a result, students and teachers continue to hold face-to-face meetings, with a one-week system of meeting and one week off. The school also does not have extracurriculars for its students, and the school building is only made of wood which is often flooded. This article is the result of research that initiated the Stikosa-AWS students community service program, in the form of developing non-academic education through extracurricular programs. In addition, students also donated items in the form of cleaning equipment for the Gebang 2 Elementary School which was poorly maintained. And donate book packages that are still fit for use.